« C’est prévu pour quand ? » - Elsa Boulet (Temporalités)
Nowadays, it is taken for granted that pregnancy can be represented by a specific time-scale, sequenced in months and trimesters, marked by thresholds (the 3-month threshold, the timing of ultrasound scans, the fetal viability threshold, etc.) and delimited by a precise prediction of the due date. This paper critically examines the quantification of the time of pregnancy from the analytical perspective developed by A. Desrosières: what conventions govern the quantification of the time of pregnancy? What are the underlying rationales? What are the effects of these quantification operations? Based on a qualitative survey conducted in two maternity hospitals in the Paris region and on a secondary analysis of the relevant literature, the article traces the genealogy of the quantification of pregnancy since the beginning of the 20th century and traces its evolution. The analysis of the conventions underpinning this quantification reveals that it is based on the idea that ovulation is the first day in the ‘life’ of a foetus, who is the primary focus of medical care. Furthermore, quantifying the time of pregnancy leads to its standardization, which is largely effective in practice and even affects physiological processes.